DAMPAK PEMILIHAN KEPALA DAERAH (PILKADA) TERHADAP DEMOKRASI: TINJAUAN KELEBIHAN DAN KEKURANGAN PILKADA SERENTAK DI INDONESIA TAHUN 2024 - Zamhasari, Zamhasari (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2024)
General Elections are a fundamental element in a democratic system, functioning as a formal mechanism for the people to express their will and elect leaders and representatives. However, the mere existence of elections is not sufficient to ensure that a country is truly democratic. Democratic elections ensure that all citizens have equal voting rights and that the election process is conducted transparently, without coercion, manipulation, or fraud. This study not only uses a survey method to collect data, but also involves interventions in data collection through questionnaires, tests, and interviews. The main objective of this research is to explore the advantages and disadvantages of the implementation of the Concurrent Regional Head Elections in 2024 and to analyze its impact on the quality of democracy in the region. The researcher adopts David Held's Participatory Democracy Theory (1987), which emphasizes the importance of active citizen participation in the political process as a fundamental basis for a healthy democracy. The results of this study are expected to provide deeper insights into how Concurrent Elections affects the dynamics of democracy in Indonesia and offer recommendations to improve the quality of political participation in the future